2012
DOI: 10.5301/jbm.2012.9583
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite polymorphism in the EGFR, NOTCH4 and E2F4 genes and their association with breast cancer risk

Abstract: The allelic distribution observed for the 3 microsatellites matched that found in other white populations, with the exception of some (AGC)n alleles in E2F4, which have not been described previously. The length of (CA)n in EGFR and (CTG)n in NOTCH4 was not associated with breast cancer (OR=0.99; 95% CI 0.59-1.37; p=0.619 and OR=1.08; 95% CI 0.71-1.65; p=0.725, respectively). Short alleles (<13 repeats) of (AGC)n in E2F4 were less frequent in women with cancer than in the control sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, a notable feature of these genes is their critical roles in the pathways of gender specific cancers. For example, E2f4 have been reported to regulate liver cancer cell survival and risk for breast cancer 18 - 20 ; Hnrnpk has been linked to the neuroendocrine differentiation signaling in prostate cancer cells 21 as well as to the development of breast cancer 22 . In brain cancer the expression of Hnrnpk has been linked to the Egfr 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a notable feature of these genes is their critical roles in the pathways of gender specific cancers. For example, E2f4 have been reported to regulate liver cancer cell survival and risk for breast cancer 18 - 20 ; Hnrnpk has been linked to the neuroendocrine differentiation signaling in prostate cancer cells 21 as well as to the development of breast cancer 22 . In brain cancer the expression of Hnrnpk has been linked to the Egfr 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Short alleles (\13 repeats) of (AGC)n in E2F4 were less frequent in women with cancer than in the control sample. Microsatellite instability of this repeat was also reported in BC [61]. Thus, besides AR gene, other genes with CAG repeats may also contribute to breast carcinogenesis, including POLG, ATN, FXN and E2F4.…”
Section: Genome-wide Cag Repeat Expansions and Breast Cancermentioning
confidence: 90%
“…3c, NMB q = 0.03), which encodes a transcription factor that plays a critical role in cell cycle regulation and binds to three known tumour suppressors, pRB, p107 and p13. When affected by microsatellite polymorphisms, E2F4 is linked to an enhanced risk for developing breast cancer 24 . Interestingly, it has also been shown that loss of E2F4 can suppress tumourigenesis 25 while its expression is needed for the proliferation of e.g.…”
Section: (Supplementarymentioning
confidence: 99%